KUALITAS PELAYANAN DAN PROMOSI PENGARUHNYA TERHADAP KEPUASAN PELANGGAN PADA AGROWISATA LEBAH ETNO BALI FOUNDATION DI DESA BAHA MENGWI - Ida Ayu Komang Juniasih; Ida Bagus Radendra Suastama; Putu Dananjaya Oka Dharma (Forum Manajemen STIMI Handayani Denpasar, 2022)
Agrotourism is an activity related to tourism activities which is also a lesson for tourists to get to know more about the production process in the agricultural sector and make the agricultural area a place to enjoy agricultural products directly. The purpose of the study was to determine the effect of service quality and promotion on customer satisfaction at the Bali Foundation's Ethno Bees Agrotourism. The types of data used in this study are qualitative data and quantitative data, with data sources namely primary data and secondary data. Methods of collecting data by means of observation, interviews, documentation and questionnaires. The results showed that there was a positive and significant influence between service quality and promotion on customer satisfaction, which means that the higher the service and promotion quality, the higher the customer satisfaction. In this case, every improvement in service quality and promotion will increase customer satisfaction. In addition, there is a positive and significant influence between service quality and promotion simultaneously on customer satisfaction at the Bali Foundation's Ethno Bee Agrotourism in Baha Mengwi Village.